Management of Educational Facilities and Infrastructure Procurement in Supporting Learning Quality in Madrasah - Istiqomah, Nurul; Santosa, Sedya (STIT Ahlussunnah Bukittinggi, 2025)
Procurement of educational facilities and infrastructure is a strategic component in education management that contributes to the quality of learning. This study aims to analyze the procurement management of educational facilities and infrastructure in supporting the quality of learning in public madrasahs. The research used a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and documentation studies involving the madrasah head, deputy head of curriculum, and teachers. Data analysis was done thematically through the stages of data reduction, data presentation, and conclusion drawing. The results show that the procurement of facilities and infrastructure is carried out systematically through the stages of planning, proposing, budgeting, implementing, and evaluating and maintaining which is carried out on an ongoing basis by involving various stakeholders and referring to applicable regulations. The planning and proposal system is integrated with learning needs, while budget management utilizes multi-source funds. Procurement implementation applies a tender mechanism to ensure efficiency, transparency and accountability. The research findings confirm that the implementation of good procurement governance principles contributes to the effectiveness of learning and improving the quality of education services in public madrasahs, and serves as a reference for education unit managers in designing a planned, accountable and quality-oriented facilities and infrastructure procurement system.